2016
DOI: 10.1007/s00216-016-9540-x
|View full text |Cite
|
Sign up to set email alerts
|

The biochemical origins of the surface-enhanced Raman spectra of bacteria: a metabolomics profiling by SERS

Abstract: The dominant molecular species contributing to the 785 nm excited SERS spectra of bacteria are the metabolites of purine degradation: adenine, hypoxanthine, xanthine, guanine, uric acid and AMP. These molecules result from the starvation response of the bacterial cells in pure water washes following enrichment from nutrient rich environments. Vibrational shifts due to isotopic labeling, bacterial SERS spectral fitting, SERS and mass spectrometry analysis of bacterial supernatant, SERS spectra of defined bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
186
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(202 citation statements)
references
References 68 publications
15
186
1
Order By: Relevance
“…The last two molecules are important in the process of cellular respiration taking place in the bacterial cell membrane and demonstrate a close interaction between SERS-active platform and cell wall/ membrane of bacteria. It should likewise be noticed that metabolites of purine degradation may also contribute to the intensity of the band at 730 cm -1 [42]. However, according to Premasiri et al the band at 1352 cm -1 (not observed in our spectra) represents a metabolic by-product like pyocyanin, a pigment that bacteria produce during their growth.…”
Section: Resultsmentioning
confidence: 47%
See 1 more Smart Citation
“…The last two molecules are important in the process of cellular respiration taking place in the bacterial cell membrane and demonstrate a close interaction between SERS-active platform and cell wall/ membrane of bacteria. It should likewise be noticed that metabolites of purine degradation may also contribute to the intensity of the band at 730 cm -1 [42]. However, according to Premasiri et al the band at 1352 cm -1 (not observed in our spectra) represents a metabolic by-product like pyocyanin, a pigment that bacteria produce during their growth.…”
Section: Resultsmentioning
confidence: 47%
“…Previously, it was shown that the dominant molecular species giving their contribution to the SERS spectra of bacteria excited at 785 nm are the metabolites of purine degradation [42]. However, slight changes of the dominant SERS bands may be caused by the presence of the additional proteins/enzymes produced by bacterial cells, which can be concluded from the SERS experiments performed with E. coli strains.…”
Section: Resultsmentioning
confidence: 99%
“…Sodium diphosphate buffer was found to generate the SERS signal faster for certain species than washing with water. 61 The samples were spun down and the rinsing process was repeated 3×. Upon completion of the third centrifugation step, the supernatant was removed to leave approximately 10 μ L of sample for SERS analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of SERS spectra together with isotopic labeling and MS resulted in dominating features of purine degradation products: adenine, hypoxanthine, xanthine, guanine, uric acid, and AMP as the bacterial cell went through the starvation process. 177 The results provided a fundamental point for the development of SERS as rapid bacterial detection as well as a mean to monitor cellular activity and the kinetic of metabolic pathway.…”
Section: Bacteriamentioning
confidence: 96%
“…177 The SERS capacity for bacterial identification as well as the biochemical origins of the vibrational fingerprints on SERS spectra was fully exploit. In general, SERS spectra of bacteria were obtained with Ag-coated SiO 2 SERS chip substrate at 785 nm, which can eliminate strong SERS signals contributed from bacterial cell wall (lipids, polysaccharides, peptidoglycan, and proteins).…”
Section: Bacteriamentioning
confidence: 99%